Control of systemic iron homeostasis by the 3’ iron-responsive element of Divalent metal transporter 1 in mice - Tybl, Elisabeth; Gunshin, Hiromi; Gupta, Sanjay; Barrientos, Tomasa; Bonadonna, Michael; Celma Nos, Ferran; Palais, Gael; Karim, Zoubida; Sanchez, Mayka; Andrews, Nancy C.; Galy, Bruno (HemaSphere, 2020)
Supplemental Digital Content is available in the text
Zuerst veröffentlicht: 23. September 2020
Gesehen am 23.06.2025